2021
DOI: 10.1111/jdv.17310
|View full text |Cite
|
Sign up to set email alerts
|

Toxic epidermal necrolysis‐like acute cutaneous graft‐versus‐host disease in a stem cell recipient – a diagnostic dilemma

Abstract: Bastuji-Garin S. [Requests for emergency appointments with dermatologists in private practice in France: the ETude Urgences en DErmatologie lib erale (ET.U.DE) study].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…Schultz et al reported a case of grade 4 GvHD who developed extensive macular rash along with mucosal ulceration within weeks of liver transplantation [1]. Similar to the letter by Klein et al, our patient developed severe mucocutaneous eruption with epidermal sloughing within the second week of HSCT [2]. Distinctively, she had diarrhea and progressive elevation in bilirubin, ALP and GGT levels favoring the gastrointestinal involvement of acute GvHD.…”
Section: Discussionsupporting
confidence: 78%
“…Schultz et al reported a case of grade 4 GvHD who developed extensive macular rash along with mucosal ulceration within weeks of liver transplantation [1]. Similar to the letter by Klein et al, our patient developed severe mucocutaneous eruption with epidermal sloughing within the second week of HSCT [2]. Distinctively, she had diarrhea and progressive elevation in bilirubin, ALP and GGT levels favoring the gastrointestinal involvement of acute GvHD.…”
Section: Discussionsupporting
confidence: 78%